Ultrasmall gold cluster arrays encapsulated in silica nanospheres: applications in fluorescence imaging and catalysis - Samanta, Anupam; Dhar, Basab B.; Devi, R. Nandini (Journal of Physical Chemistry C, 2012)
Facile synthesis of ultrasmall gold nanoclusters of size <2 nm dispersible in water using a novel quaternary ammonium ligand is reported. Further, arrays of these nanoclusters are encapsulated in monodisperse silica nanospheres of size 25-30 nm. The photophysical characteristics of the clusters are found to be intact upon encapsulation, rendering the resulting composite material ideal for fluorescence imaging applications. We have further shown the utilization of these materials in catalysis as precursors for Au nanopartides encapsulated in porous silica.

Understanding the electron transfer process in ZnO-naphthol azobenzoic acid composites from photophysical characterisation - George, Leena; Kunhikannan, Athira K.; Illathvalappil, Rajith; Ottoor, Divya; Kurungot, Sreekumar; Devi, R. Nandini (Physical Chemistry Chemical Physics, 2016)
Semiconductor nanoparticles surface modified with organic molecules capable of visible light absorption and effectively transferring the electrons to the catalytic sites have the potential to be good photocatalysts. ZnO nanoparticles of size similar to 3 nm are grafted with two azonaphthols, one conjugated and the other non-conjugated. The photophysical properties of modified ZnO indicate an effective electron transfer from the conjugated azonaphthol to ZnO but not in the case of the non-conjugated molecule. It is also observed from lifetime studies that the conjugated molecule stabilises the defect sites on ZnO nanoparticles. It is possible that excited electrons from the conjugated molecule are transferred to specific defect sites in ZnO. This apparently does not occur in the non-conjugated molecule, bringing to focus the importance of the photophysical characteristics of organic modifiers in designing visible light active photocatalysts.

Ultra small nanoclusters to nanoparticles: fine tuning of particle size in water dispersible cation functionalized thiolate protected Pd system - Dhanraj, Prakriti; Samanta, Anupam; Devi, R. Nandini (Materials Today-Proceedings, 2017)
Monolayer protected noble metal nanoparticles have attracted considerable attention in the past decade with potential applications in fields ranging from catalysis to biosensors [1, 2,]. We have developed a novel procedure for the synthesis of water dispersible Pd nanoparticles based on a bifunctional ligand, N,N,N-tripropyl(11-mercaptoundecyl) ammonium chloride in which thiol group binds to the metal, hydrophobic middle alkyl chain acts as capping agent and provides steric stability and on the other end the ammonia group helps in making nanoparticles hydrophilic. In this paper, we report the fine-tuning of size of water dispersible Pd nanosystems ranging from clusters to nanoparticles by adjusting the synthetic parameters and their characterization. (C) 2017 Elsevier Ltd. All rights reserved.

Understanding alloy structure and composition in sinter-resistant AgPd@SiO2 encapsulated catalysts and their effect on catalytic properties - Mondal, Sourik; Rajesh, Thattarathody; Dhar, Basab B.; Snellman, Markus; Li, Junjie; Deepak, Francis Leonard; Devi, R. Nandini (New Journal of Chemistry, 2017)
The extent of alloying and the alloy composition, which are crucial in determining the activity and selectivity of bimetallic catalysts, were studied in porous silica encapsulated AgPd catalysts using XRD, HRTEM and HAADF-STEM. Water-dispersible ligand protected Pd ultra-small clusters and Ag nanoparticles of three different sizes were used as the precursors. The high reactivity of Pd ultra-small clusters enhanced the alloying of larger Ag nanoparticles to some extent. Encapsulation appeared to have minimised the sintering of the resultant nanoparticles. The earlier suggestions of the role of d-band positions with respect to adsorption energies holds good for the AgPd system and alloying enhances the activity. Alloy with the composition of Ag50Pd50 was found to be the most active with the reaction rate enhanced two fold compared to that in other compositions. Other factors like particle size and sinter-resistance also played important roles in enhancing the activity of these catalysts.

Understanding alloy structure and composition in sinter-resistant AgPd@SiO2 encapsulated catalysts and their effect on catalytic properties (vol 41, pg 14652, 2017) - Mondal, Sourik; Rajesh, Thattarathody; Dhar, Basab B.; Snellman, Markus; Li, Junjie; Deepak, Francis Leonard; Devi, R. Nandini (New Journal of Chemistry, 2020)

Ultra-small Au nanoclusters with tailored photoluminescence properties using modified thiol ligands: a computational and experimental demonstration - Chahande, Anurag M.; Maibam, Ashakiran; Krishnamurty, Sailaja; Devi, R. Nandini (Particle & Particle Systems Characterization, 2024)
Au nanoclusters with tailored photoluminescence can be obtained through controlled nanoparticle ligand interface chemistry. The present work reports molecular gold nanoclusters with tuneable photoluminescence emission from 600 to 700 nm using N,N `,N `'-trialkyl (11-mercaptoundecyl)ammonium chloride ligands as capping-agents. The tunability within red spectral region is regulated through specific interface chemistry between gold nanoclusters of molecular range and functional groups of the quaternary ammonium head over N,N `,N `'-trialkyl(11-mercaptoundecyl)ammonium chloride. Combined understanding obtained from the spectroscopy, microscopy, and density functional theory studies demonstrate that the functional group specific electronic interactions at the interfaces steer the emission characteristics of ``molecular'' Au nanoparticles. The study clearly identifies that bulkier functional groups, i.e., triethyl, tripropyl, tributyl, and dimethyl benzene over N+ (of thiol ligand) through their steric effects minimize the particle size giving rise to tunable photoluminescence emission in red spectral region. However, the red shift seen in the emission Au nanoclusters with N-(11-mercaptoundecyl)-N,N `-dimethylbenzenammonium chloride ligand in contradiction to particle size effect is computationally proved to be due to the delocalization of electron density from benzene aromatic ring to N+ of ammonium head leading to a reduction in the HOMO-LUMO energy gap. Fluorescence properties of water dispersible Au nanoclusters are tuned by varying the ammonium head group. Density Functional Theory studies correlate the distinction in emission when head group is phenyl to charge transfer characteristics. image
Keywords: Density functional theory; photoluminescent Au nanoclusters; surface plasmon resonance; thiol ligand

Understanding the structural characteristics of modified ceramic hollow fiber oxygen transport membranes through in silico tomography simulation study - Jogdand, Shunottara M.; Sharma, Jyoti; Khilari, Rushikesh S.; Mahajan, Digvijay P.; Patil, Prashant; Pol, Harshavardhan V.; Torris, Arun; Agrawal, Ravi; Kharul, Ulhas K.; Devi, R. Nandini (ACS Applied Materials & Interfaces, 2025)
Design and development of integrated membrane reactor systems are gaining attention as a sustainable solution capable of performing multiple functions in a single reactor. Membrane reactors made of mixed ionic-electronic conduction materials dosing pure O to the reactions can be exploited for various catalytic processes. In this case, micro- and macrostructures of the membrane surface play a significant role in the permeation performance of membranes, and understanding these parameters prior to scaling up to modules is imperative. Here, 3D X-ray tomography imaging, a versatile nondestructive instrumental technique, is used in understanding the structural behavior of the membrane walls at different structural alignments, leading to anticipation of fouling areas upon assembling membrane reactors. La0.6Sr0.4Co0.2Fe0.8O3-delta hollow fiber membranes are fabricated by the phase inversion method and further modified by the optimized acid etching technique. In silico simulations on different morphologies before and after surface modifications are carried out under varying flow rates at nonambient temperatures to mimic real experimental conditions. Critical parameters such as gas velocity, pressure exerted on cavity walls, and strain, dictating structural integrity of the fibers under experimental conditions, were evaluated. As a result of the assessment, the surface-modified structural morphology with finger-like cavities initiating from the inner wall of the membrane was found to be robust. Increase in the pore size, nonuniform pore size distribution, and irregular and interdigitated cavities formed in outer fingered membranes after multiple surface treatments led to an similar to 5 fold increase in the average pressure exerted at the cavity walls when compared to inner fingered membranes. Strain profile generated for inner fingered membranes shows homogeneous distribution of strain for the applied stress throughout the 3D geometry of the membrane. This detailed structural analysis of the membrane will help in building a more robust and efficient system for scale-up applications.
Keywords: 3D X-ray tomography; in silico simulation; oxygen transport membranes; perovskite; phase inversionmethod